Komparasi Model Prediksi Financial Distress (Studi Kasus Pada Industri Barang Konsumsi yang Terdaftar di Bursa Efek Indonesia periode 2017-2018) - Purdana Wahyu Hidayat; Dwi Ari Pertiwi (Prodi Akuntansi Fakultas Ekonomi Universitas Hasyim Asy'ari, 2020)
The Consumer goods industry is one of the bigest contributors to the state budget, so the condition of every consumer goods company in Indonesia are of particular concern to the government. This study aims to determine how the extent of financial distress of consumer goods companies IDX 2017 – 2018. The population in this study were every consumer goods company registered in IDX for the period 2017-2018 and 41 samples were obtained. data collection methods namely purposive sampling. The data analysis technique used with Altman method, Springate method, Grover method and Zmijewski method. The results of the calculation with fourth method there are some consumer goods industry companies were classified in financial distress and obtained the result that the Springate method is the most useful methods in predicting financial distress.